2011
DOI: 10.4158/ep10131.or
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Effects on Glucose Tolerance and Insulin Sensitivity in Persons at Risk for Diabetes Mellitus

Abstract: Objective To investigate the effects of daily chromium picolinate supplementation on serum measures of glucose tolerance and insulin sensitivity in patients at high risk for type 2 diabetes mellitus. Methods We conducted a randomized, double-blind, placebo-controlled, modified cross-over clinical trial with 6-month sequences of intervention and placebo followed by a 6-month postintervention assessment. Adult patients with impaired fasting glucose, impaired glucose tolerance, or metabolic syndrome were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Chromium (Cr) is a well-known TE, that displays a major role in carbohydrates, lipids and proteins, and its deficiency seems to be associated with Type 2 Diabetes Mellitus (1,3,26) . Cr acts by reducing insulin resistance, being part of a Glucose Tolerance Factor (GTF) that also includes nicotinic acid, glycine, cysteine and glutamic acid (1,4,5,11,14,18,19,22) . Also, Cr may participate in lipid metabolism and may have some effect on body composition.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium (Cr) is a well-known TE, that displays a major role in carbohydrates, lipids and proteins, and its deficiency seems to be associated with Type 2 Diabetes Mellitus (1,3,26) . Cr acts by reducing insulin resistance, being part of a Glucose Tolerance Factor (GTF) that also includes nicotinic acid, glycine, cysteine and glutamic acid (1,4,5,11,14,18,19,22) . Also, Cr may participate in lipid metabolism and may have some effect on body composition.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies suggested that chromium supplements, particularly niacin-bound chromium and/or chromium-nicotinate, may be effective in attenuating insulin resistance and lowering plasma cholesterol levels [17]. In contrast,a few of studies showed that chromium supplementation did not improve glycemic control in type 2 diabetes [33,34]. Nevertheless, most research believed that supplemental Cr is beneficial to diabetes patients [16,17,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies in patients with newly diagnosed T2DM found that dietary supplementation with 42 lg chromium (as 9 g of brewer's yeast) over 3 months generated significant reductions of plasma glucose and glycated hemoglobin (HbA1c), with a concomitant positive impact on plasma lipids [19]. However, studies in patients with longer-duration T2DM have not found a positive effect of chromium supplementation [20]. Mechanistically, chromium supplementation appears to reduce plasma levels of proinflammatory cytokines and oxidative stress [21].…”
Section: Trace Elementsmentioning
confidence: 99%